Game rules vs. fandom. How Nintendo’s Animal Crossing fan-made content negotiates the videogame meanings - Moreno, Jose A. (Ámbitos. Revista Internacional de Comunicación, 2020)
This research reviews the ideologies present in the Nintendo’s videogame saga Animal Crossing and aims to discover how fans interpret them. The process involves an exploration of the online fanart of the videogame and its classification into reproductive, neutral or critical fandom, depending on the revised operating ideologies. Following, a content analysis and brief semiotic analysis have been conducted to interpret the meanings that fans elaborated and wanted to share with the community. As a result, this research shows that the fandom of Animal Crossing reinterprets the ideologies of the game producing a critique of struggles present in society against sexism and consumerism. However, some fanart is aligned with the neoliberal and sexist ideas that emanate from the canonical text. Thus, analysing fandom’s production is a worth way to discover how audiences interact with videogames and how they expand its meanings beyond the game.